Wordwall as a Digital Tool for Promoting Students’ Learning Engagement - Ririn Mahriatus Solihat; Dina Rachmawati (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2026)
In the field of English as a Foreign Language (EFL) education, digital learning media has become a valuable tool to promote student learning engagement. One such platform, Wordwall, integrates gamification to support interactive and enjoyable learning experiences. This research explores the use of Wordwall in the Jump Start class at FL Haus Indonesia, aiming to analyze its effectiveness in promoting student engagement. Using a qualitative exploratory case study, data were collected through classroom observations, interviews, questionnaires, and documentation. The findings showed that Wordwall significantly promotes student engagement across cognitive, emotional, and behavioral dimensions. Cognitively, students showed better understanding of the material; emotionally, they expressed increased motivation and enjoyment; and behaviorally, they participated more actively during learning activities. Teachers found Wordwall useful for delivering material, especially in teaching vocabulary and grammar. It concludes that Wordwall is a digital learning media that can promote student learning engagement—cognitively, emotionally, and behaviorally. This research encourages further studies to examine Wordwall application in broader educational contexts.